Energy balance‐related factors in childhood and adolescence and risk of colorectal cancer expressing different levels of proteins involved in the Warburg‐effect. Issue 11 (5th February 2022) - Jenniskens, Josien C. A.; Offermans, Kelly; Simons, Colinda C. J. M.; Samarska, Iryna; Fazzi, Gregorio E.; Smits, Kim M.; Schouten, Leo J.; Weijenberg, Matty P.; Grabsch, Heike I.; van den Brandt, Piet A.
Abstract: Early‐life (childhood to adolescence) energy balance‐related factors (height, energy restriction, BMI) have been associated with adult colorectal cancer (CRC) risk. Warburg‐effect activation via PI3K/Akt‐signaling might explain this link. We investigated whether early‐life energy balance‐related factors were associated with risk of Warburg‐subtypes in CRC. We used immunohistochemistry for six proteins involved in the Warburg‐effect (LDHA, GLUT1, MCT4, PKM2, P53, and PTEN) on tissue microarrays of 2399 incident CRC cases from the prospective Netherlands Cohort Study (NLCS). Expression levels of all proteins were combined into a pathway‐based sum score and categorized into three Warburg‐subtypes (Warburg‐low/‐moderate/‐high). Multivariable Cox‐regression analyses were used to estimate associations of height, energy restriction proxies (exposure to Dutch Hunger Winter; Second World War [WWII]; Economic Depression) and adolescent BMI with Warburg‐subtypes in CRC. Height was positively associated with colon cancer in men, regardless of Warburg‐subtypes, and with Warburg‐low colon and Warburg‐moderate rectal cancer in women. Energy restriction during the Dutch Hunger Winter was inversely associated with colon cancer in men, regardless of Warburg‐subtypes. In women, energy restriction during the Hunger Winter and WWII was inversely associated with Warburg‐low colon cancer, whereas energy restriction during the Economic Depression was positively associated with Warburg‐high colon cancer. Adolescent BMI was positively associated with Warburg‐high colon cancer in men, and Warburg‐moderate rectal cancer in women. In conclusion, the Warburg‐effect seems to be involved in associations of adolescent BMI with colon cancer in men, and of energy restriction during the Economic Depression with colon cancer in women. Further research is needed to validate these results. Abstract : What's new? Early‐life energy balance‐related factors, such as height, energy restriction and body mass index (BMI), are associated with colorectal cancer (CRC) risk later in life. The mechanisms behind these associations, however, remain unknown. Here, using data from the prospective Netherlands Cohort Study (NLCS), the authors investigated the involvement of the Warburg‐effect in associations between early‐life energy balance‐related factors and CRC risk. Analyses suggest that the Warburg‐effect is involved in associations of adolescent BMI and colon cancer risk in men.